Band Structure Engineering in MoS2 Based Heterostructures toward High‐Performance Phototransistors. Issue 13 (7th May 2020) - Ying, Haoting; Li, Xin; Wang, Hemiao; Wang, Yurui; Hu, Xin; Zhang, Jian; Zhang, Xuefeng; Shi, Yueqin; Xu, Minxuan; Zhang, Qi
Abstract: Interfacial band structure engineering paves a promising route to promote the application of 2D semiconductors in optoelectronics, and thereby in the last decades, a great number of studies about heterojunction based on transition‐metal dichalcogenides (TMDs) have been implemented. Most of the latest photodetectors mainly consist of a type II band alignment in which, however, the interfacial emission quenching leads to a higher nonradiative rate, an awkward problem for reducing their energy consumption. Here, BaTiO3 /MoS2 heterostructures with type I band alignment fabricated by a facile spin‐coating method are reported, and their remarkable photodetection performance in comparison with devices based on bare MoS2 ( Rλ : 120 A W −1 vs 1.7 A W −1 and external quantum efficiency (EQE): 4.78 × 10 4 % vs 4.5 × 10 2 % @365 nm) is demonstrated. Optical measurements including micro‐Raman and photoluminescence (PL) suggest a carrier extraction process accompanied by the carrier injection occurring in the narrower‐bandgap (MoS2 ) layer, responsible for the increment of carrier population in MoS2 channel and subsequent improvement of detection ability. Hence, the demonstration of such 0D/2D type‐I heterostructures through an interfacial control provides valuable information for developing low cost yet superior performance optoelectronic devices in future. Abstract : An improved photodetector based on BaTiO3 /MoS2 heterostructures with type I band alignment is demonstrated compared to bare MoS2 ( Rλ : 120 vs 1.7 A W −1 ; external quantum efficiency (EQE): 4.78 × 10 4 % vs 4.5 × 10 2 % @365 nm). Optical measurements suggest that a carrier extraction process accompanied by carrier injection occurs in the MoS2 layer, leading to the increasing carrier population in channel.